Characterization of a novel KCNJ2 sequence variant detected in Andersen-Tawil syndrome patients - Stefanie Scheiper; Brigitte Hertel; Britt-Maria Beckmann; Stefan Kääb; Gerhard Thiel; Silke Kauferstein (BMC, 2017)
Abstract Background Mutations in the KCNJ2 gene encoding the ion channel Kir2.1 have been linked to the Andersen-Tawil syndrome (ATS). Molecular genetic screening performed in a family exhibiting clinical ATS phenotypes unmasked a novel sequence variant (c.434A > G, p.Y145C) in this gene. The aim of this study was to investigate the effect of this variant on Kir2.1 ion channel functionality. Methods Mutant as well as wild type GFP tagged Kir2.1 channels were expressed in HEK293 cells. In order to examine the effect of the new variant, electrophysiological measurements were performed using patch clamp technique. Cellular localization of the mutant in comparison to the wild type ion channel was analyzed by confocal laser scanning microscopy. Results The currents of cells expressing only mutant channels or a mixture of wild type and mutant were significantly reduced compared to those expressing wild type (WT) channels (p < 0.01). Whereas WT expressing cells exhibited at −120 mV an averaged current of −4.5 ± 1.9 nA, the mutant generates only a current of −0.17 ± 0.07 nA. A co-expression of mutant and WT channel generates only a partial rescue of the WT current. Confocal laser scanning microscopy indicated that the novel variant is not interfering with synthesis and/or protein trafficking. Conclusions The detected sequence variant causes loss-of-function of the Kir2.1 channel and explains the clinical phenotypes observed in Andersen-Tawil syndrome patients.